Velocity of the partical changes with time in seconds as v=(t-4)m/s .average velocity of the partical in the interval (0-6)second is
Answers
Answered by
1
Here velocity varies with time, so average velocity can be found by
![\bold{\ \textless \ v\ \textgreater \ =\frac{\int\linits^a_b{v(t)}\,dt}{\int\limits^a_bdt}} \bold{\ \textless \ v\ \textgreater \ =\frac{\int\linits^a_b{v(t)}\,dt}{\int\limits^a_bdt}}](https://tex.z-dn.net/?f=%5Cbold%7B%5C+%5Ctextless+%5C+v%5C+%5Ctextgreater+%5C+%3D%5Cfrac%7B%5Cint%5Clinits%5Ea_b%7Bv%28t%29%7D%5C%2Cdt%7D%7B%5Cint%5Climits%5Ea_bdt%7D%7D)
here is the average velocity of particle .
Now, < v > =![\bold{\ \textless \ v\ \textgreater \ =\frac{\int\linits^6_0{(t-4)},dt}{\int\limits^6_0dt}} \bold{\ \textless \ v\ \textgreater \ =\frac{\int\linits^6_0{(t-4)},dt}{\int\limits^6_0dt}}](https://tex.z-dn.net/?f=%5Cbold%7B%5C+%5Ctextless+%5C+v%5C+%5Ctextgreater+%5C+%3D%5Cfrac%7B%5Cint%5Clinits%5E6_0%7B%28t-4%29%7D%2Cdt%7D%7B%5Cint%5Climits%5E6_0dt%7D%7D+)
= [t²/2 - 4t]⁶₀/[t]⁶₀
= [36/2 - 24]/[6]
= (18 - 24)/6
= -6/6
= -1
Hence, average velocity = -1 m/s
here is the average velocity of particle .
Now, < v > =
= [t²/2 - 4t]⁶₀/[t]⁶₀
= [36/2 - 24]/[6]
= (18 - 24)/6
= -6/6
= -1
Hence, average velocity = -1 m/s
Similar questions